Tinjauan Kuat Lentur Balok BetonDengan Tulangan Model Rangka Dari Kayu MerantiDengan Variasi Jarak Antar Begel - Sugiyono, Sapto; , Basuki, S.T, M.T; , Ir. Abdul Rochman, M.T (2016)
Reinforced concrete beams is one part of building construction whose strength depends on the quality of concrete and steel reinforcement in it. Concrete reinforcement generally consists of flexural and shear reinforcement. Flexural mounted horizontally on the beam axis serves as a barrier bending moment. Whereas shear or stirrup mounted transverse to the beam axis, serves as a barrier shear force. Concrete beams with reinforcement frame models are basically the same with ordinary steel reinforced concrete beams. The difference between the two is the reinforcement of concrete beams using no additional reinforcement frame models skew between the vertical bars that serve structurally. This study modifies the main reinforcement and shear reinforcement that usually use steel reinforcement is replaced with reinforcement of meranti wood frame models and further testing on the beam flexural strength and the results are then compared with the flexural strength of concrete blocks using ordinary steel reinforcement. This study using concrete with a strong plan of 20 MPa, the test object beam measuring 10 cm x 20 cm x 120 cm. flexural / primary and shear einforcement using steel diameter 6 mm and 4 mm. The test results obtained show no difference in the flexural strength of concrete beams bertulangan steel reinforcement concrete beams using the model order of meranti wood, and the difference in flexural strength ranging between (32.47% - 69.72%)